Finite Element Study of the Effect of Interfacial Gaps on the in-Plane Behaviour of Masonry Infills Bounded by Steel Frames. (May 2017) - Chen, Xi; Liu, Yi
Abstract: A finite element study was conducted to investigate the in-plane behaviour and strength of concrete masonry infills bounded by steel frames with the focus on the effect of interfacial gaps. Various gap locations and sizes were studied. The results showed that the top beam-infill gap was more detrimental to the stiffness and strength of infill than the column-infill gaps. Gap(s) had less effect on infills bounded by weak frames than strong frames. Different arrangements of gap locations at the column-infill interface affected the behaviour of infilled frames only when the friction coefficient exceeded 1.0. The provisions contained in the American masonry standard MSJC 2013 for design of infilled frames with gaps were examined. It was found that in most cases, the reduction factor for the gap effect specified in the MSJC 2013 produced conservative estimates for both the stiffness and strength. Based on the finite element results, a set of lower bound expressions for stiffness and strength evaluation over a wide range of gap size and locations were proposed.